Strategic Management of Technology-Based Curriculum Development to Enhance Digital Literacy in Elementary Schools in Indonesia: A Deep Learning Approach to Learning - Usman Jayadi; Abhilash Oji (International Journal of Social Science, Education, Communication and Economics (SINOMICS Journal), 2025)
This study explores the strategic management of technology-based curriculum development to enhance digital literacy in Indonesian elementary schools, focusing on the role of deep learning in transforming educational practices. In the digital age, fostering digital literacy from a young age has become essential for preparing students for future success. The research examines the challenges and opportunities in integrating technology into the curriculum, particularly in schools with varying levels of access to digital resources. Through qualitative methods, including interviews with educators, curriculum developers, and policymakers, as well as classroom observations, the study identifies key barriers such as inadequate infrastructure, limited teacher training, and resistance to technological change. However, it also highlights the potential of deep learning technologies to personalize learning experiences, improve student engagement, and enhance digital literacy outcomes. The findings suggest that strategic curriculum management, coupled with teacher involvement in the development process and targeted professional development, is critical for successful technology integration. The study provides actionable recommendations for policymakers and educators to enhance digital literacy and bridge the digital divide in Indonesian schools, emphasizing the need for a comprehensive, long-term strategy that leverages both technological and pedagogical advancements.